2009
DOI: 10.1111/j.1745-7599.2008.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of modified jazz dance on balance, cognition, and mood in older adults

Abstract: Because falls are a leading cause of morbidity and mortality in older adults of both genders, research is needed to evaluate both the impact of jazz dance on balance in older men and jazz dance as a fall prevention strategy in aging adults. Additionally, longitudinal research with a larger sample size is needed to test the effectiveness of jazz dance as a strategy for improving balance, cognition, and mood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
2
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 32 publications
6
63
2
14
Order By: Relevance
“…As shown in Table 4, Alpert et al (2009) did not find any positive association between cognitive function and jazz group classes in older people living in communities. However, the study included only 13 participants and no controls.…”
Section: Intervention Studiesmentioning
confidence: 44%
See 1 more Smart Citation
“…As shown in Table 4, Alpert et al (2009) did not find any positive association between cognitive function and jazz group classes in older people living in communities. However, the study included only 13 participants and no controls.…”
Section: Intervention Studiesmentioning
confidence: 44%
“…There are multiple studies that have shed a positive light on the impact of dance related interventions and healthy aging for both the cognition and physical capacity domains. The type of dance did not seem to make any difference; a broad range of different types of dance, ranging from folklore dance, through tango to salsa and jazz, showed beneficial effects (Alpert et al, 2009;Coubard et al, 2011;Currie et al, 2012;Dechamps et al, 2010;Fosshage, 2004;Granacher et al, 2012;Gray, 2008;Heiberger et al, 2011;Keogh et al, 2009;Kim et al, 2011;Koch and Bräuninger, 2005;Sevdalis and Keller, 2011).…”
Section: Effects Of Dance and Movement Interventionsmentioning
confidence: 93%
“…[16][17][18][19] Musical exercise improves cognitive function, mood and behavior in patients with all stages of Alzheimer's disease suggesting that dancing interventions are potentially far more than entertainment activity. [20][21][22][23] Argentine tango may be particularly helpful for improving balance and functional mobility in patients with PD.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of efficiency of neuro muscular connections and slowing of information processing leads to slower reaction time and locomotor adjustments, this in turn results in maintaining body's balance during static and dynamic movements thus to slow this deterioration of balance one should gradually and continuously stimulate balance through motor activity. Many studies have reported that dance based exercises/ therapy improves balance and gait in elderly individuals [22,17,16], but these are behavioral studies show functional modifications in balance system. Hence from the present study it can be postulated from the objective method that dance based therapy/exercises can be used to reduce fall risks in elderly in order to have significant psycho social benefits and improve their perception of their life.…”
Section: Discussionmentioning
confidence: 99%